Pneumonia initiates a tauopathy. Issue 9 (12th August 2021) - Balczon, Ron; Lin, Mike T.; Lee, Ji Young; Abbasi, Adeel; Renema, Phoibe; Voth, Sarah B.; Zhou, Chun; Koloteva, Anna; Michael Francis, C.; Sodha, Neel R.; Pittet, Jean‐Francois; Wagener, Brant M.; et al.
Abstract: Pneumonia causes short‐ and long‐term cognitive dysfunction in a high proportion of patients, although the mechanism(s) responsible for this effect are unknown. Here, we tested the hypothesis that pneumonia‐elicited cytotoxic amyloid and tau variants: (1) are present in the circulation during infection; (2) lead to impairment of long‐term potentiation; and, (3) inhibit long‐term potentiation dependent upon tau. Cytotoxic amyloid and tau species were recovered from the blood and the hippocampus following pneumonia, and they were present in the extracorporeal membrane oxygenation oxygenators of patients with pneumonia, especially in those who died. Introduction of immunopurified blood‐borne amyloid and tau into either the airways or the blood of uninfected animals acutely and chronically impaired hippocampal information processing. In contrast, the infection did not impair long‐term potentiation in tau knockout mice and the amyloid‐ and tau‐dependent disruption in hippocampal signaling was less severe in tau knockout mice. Moreover, the infection did not elicit cytotoxic amyloid and tau variants in tau knockout mice. Therefore, pneumonia initiates a tauopathy that contributes to cognitive dysfunction.